Three condensed importance of interfunctional communication for the acceptance of CRM system - Muhammad Ashraf; Asad Afzal Humayon; Jamil Ahmad; Mazhar Abbas (Cogent Business & Management, 2017)
Customer relationship management (CRM) is an IT-based system that manage customer long-term relationship, and also inter-functional relationship within the organization with the ultimate purpose of creating customer value by sharing concise, sufficient, accurate, timely, and reliable information. The purpose of this paper is to analyze how different kinds of communication: inter-personal interaction (IPI), written interaction (WI), and collaboration (CB) affect (i) the perceived ease of use (PEU), (ii) the perceived usefulness (PU) and ultimately (iii) the acceptance of CRM? And proposes a research model representing the relationships among WI, IPI, CB, PEU, PU, and involvement. Data collected through online survey from 210 large companies in Pakistan are analyzed. Result shows that IPI instead of collaboration has significant positive effect on PEU and PU and play important role in the acceptance of CRM system. But, WI should be viewed with more caution, because it showed negative relationship. Moreover, PEU and PU of CRM system have direct significant positive influence on involvement of marketing in the planning, implementation, and usage of CRM system that result in CRM system acceptance. The study provides theoretical and practical contributions, and also future research areas are highlighted for potential researchers.
Keywords: 650